2020
DOI: 10.1515/abm-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of maternal health services utilization in Pakistan: the role of socio-demographic characteristics

Abstract: BackgroundHigh-quality prenatal care has a significant positive impact on maternal and infant health as it helps timely diagnosis and treatment of pregnancy complications.ObjectiveTo examine factors associated with the utilization of maternal health care using the optimal count regression model.MethodsA sample of 16,314 women of reproductive ages (15–49) was used. Andersen and Newman's behavioral model of health services utilization was employed for the selection of covariates. Poisson, negative binomial, zero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Antenatal care is an important factor for not only the mother's health but also plays a crucial role in the baby's health during the early days after birth (Aslam, Sadiq, & Mehmood, 2020). Women who use antenatal care services are more likely to deliver in an institution as compared to their counterparts (Ram & Singh, 2006).…”
Section: Empirical Modelmentioning
confidence: 99%
“…Antenatal care is an important factor for not only the mother's health but also plays a crucial role in the baby's health during the early days after birth (Aslam, Sadiq, & Mehmood, 2020). Women who use antenatal care services are more likely to deliver in an institution as compared to their counterparts (Ram & Singh, 2006).…”
Section: Empirical Modelmentioning
confidence: 99%
“…Further influencing factors identified in the literature include the wealth status (Aslam, Sadiq, & Mehmood, 2020;Mosiur Rahman et al, 2011;Ndugga et al, 2020;Sultana & Shaikh, 2015;Yaya, Da, Wang, Tang, & Ghose, 2019) age, material status of women (Akibu et al, 2018;Babalola & Fatusi, 2009;Izudi, Akwang, & Amongin, 2017;Mohan et al, 2015;Rutaremwa, Wandera, Jhamba, Akiror, & Kiconco, 2015), health care facilities and distance from the clinic (Babalola & John, 2012;Dahiru & Oche, 2015;Rutaremwa et al, 2015), birth order and place of delivery (Akibu et al, 2018;Mohan et al, 2015). Religion is influential factor shaping customs and beliefs, norms which impact the decision on either attaining PNC as the study revealed that Muslim women were more reluctant to receive PNC than women belong to other religious G. Postnatal care Health Infrastructure (Barman, Saha, & Chouhan, 2020;Woldemicael & Tenkorang, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have assessed the significant influential factors of antenatal care attendance in Pakistan without considering the frequency of ANC [ 4 , 5 ]. Poisson regression, negative binomial regression, zero-inflated, and hurdle regression models have been commonly used to model the count of ANC visits [ 6 , 7 ]. Binary logistic regression and a multinomial logistic regression model are also found to study the use and ranks of ANC visits [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%